A religious building complex in the ancient settlement of Tayma (North-West Arabia) during the Nabataean period: changes and transformations - Lora, Sebastiano (Syria, 2017)
In the centre of ancient Tayma, Saudi-German excavations revealed a large temple (Building E-b1) which had been founded during the 2nd part of the 1st millennium bc and was in use until the Late Roman period. Altogether five major building stages have been identified (E-b1:3a-e). Located within a 1,700 m2 walled district, the more-than-500 m2 large building was subsequently connected with a nearby well by a tunnel. In addition to Aramaic inscriptions and monumental statues by rulers of the dynasty of Lihyan, a number of installations have been recorded illuminating the activities within and outside of the building which were connected to the use and display of water. During the Nabataean period the temple underwent major rebuilding operations adding new columns and stone-paved floors. This contribution discusses the archaeological stratigraphy of the temple and its contexts at the same time offering hypotheses on its chronological sequence including the pottery record from deposits both inside and outside of the building.